Accumulation the art, architecture, and media of climate change - Axel, Nick ca. 20. Jh; Barber, Daniel A. ca. 20./21. Jh; Hirsch, Nikolaus 1964-; Vidokle, Anton 1965- (University of Minnesota Press, 2022)
"How can climate become visible, culturally and politically? The essays in Accumulation offer a response to the relative invisibility of the climate now seen as material manifestations of social behavior"--
Contributors: Emily Apter; Hans Baumann; Amanda Boeztkes; Dominic Boyer; Lindsay Bremner; Nerea Calvillo; Beth Cullen; T. J. Demos; Jeff Diamanti; Jennifer Ferng; Jennifer Gabrys; Ian Gray; Gökçe Günel; Orit Halpern; Gabrielle Hecht; Cymene Howe; Wendy Hui Kyong Chun; Robin Kelsey; Bruno Latour; Hannah le Roux; Stephanie LeMenager; Nashin Mahtani; Kiel Moe; Karen Pinkus; Stephanie Wakefield; McKenzie Wark; Kathryn Yusoff [davon sechs TagungsteilnehmerInnen]
Keywords: Medien; Architektur; Kunst; Klimaänderung; Climatic changes in mass media / Congresses; Mass media and architecture / Congresses; Visual communication / Social aspects / Congresses; Architecture and climate / Congresses; Climat / Changements, dans les médias / Congrès; Médias et architecture / Congrès; Communication visuelle / Aspect social / Congrès; Architecture et climat / Congrès; Architecture and climate; Climatic changes in mass media; Mass media and architecture; Visual communication / Social aspects; Essay; essays; Conference papers and proceedings; Essays; Essais; Aufsatzsammlung